Legal protection of authors against unfair economic exploitation in Malaysia / Nurr Audhatul Jannah Zabidin … [et al.] - Zabidin, Nurr Audhatul Jannah; Karib, Nur Liyana Zainal; Halim, Amrah; Azhar, Amira (2013)
This project paper discusses the legal position of authors in Malaysia specifically in terms of their economic rights. The project paper consists of the outlines of our research proposal which comprises of the layout in conducting and completing the research. It also includes several laws applicable in Malaysia as well as other countries which give legal protections to authors. Further, this project paper discusses the landmark cases which have significance to the application of copyright law in Malaysia. In addition, the project paper includes the responses and comments from authors and publishers generated by interviews. Last but not least, this project paper contains recommendations and solutions in order to prevent future dispute between authors and publishers.